Syntax or nothing: Some theoretical and empirical remarks on implicit arguments - Saab, Andrés Leandro (2014)
I show that core implicit subjects in Spanish (i.e., agentive subjects in analytical passives, impersonal "se", and analytical "hacer" causatives) can be derived from a theory under which absence of Merge in external subject position is a possible syntactic output. Core implicit arguments then have no syntactic representation (pace Landau 2010). Absence of Merge gives rise to two different scenarios: (i) a conflict at the interfaces, which requires the implementation of some repair strategy, (ii) no conflict at the interfaces. The first scenario is illustrated with reference to the so-called impersonal "se" in Spanish, and the second one with reference to analytical passives. This system is able to capture a set of very intricate facts that hitherto has not had a satisfactory solution. Crucially, this particular view on implicit arguments, together with a purely syntactic theory of argument structure, explains the full distribution of impersonals and reflexives in "hacer" causative contexts. Finally, it is shown that the arbitrary readings that the two scenarios above described display have a different source: whereas impersonal "se" requires (costly) default computation at the interface, arbitrary interpretations in analytical passives are calculated at the vP level.